Analysis of uni and bi-parental markers in mixture samples: Lessons from the 22nd GHEP-ISFG Intercomparison Exercise. (November 2016) - Toscanini, U.; Gusmão, L.; Álava Narváez, M.C.; Álvarez, J.C.; Baldassarri, L.; Barbaro, A.; Berardi, G.; Betancor Hernández, E.; Camargo, M.; Carreras-Carbonell, J.; Castro, J.; Costa, S.C.; et al.
Highlights: Analysis of mixture samples from the 22nd GHEP-ISFG intercomparison exercise. Autosomal, Y and X STRs, mtDNA results analyzed. Drop-out and drop-in alleles were the main cause of errors for STRs. Nomenclature, contamination and sample mix-up issues detected in mtDNA analyses. Abstract: Since 1992, the Spanish and Portuguese-Speaking Working Group of the ISFG (GHEP-ISFG) has been organizing annual Intercomparison Exercises (IEs) coordinated by the Quality Service at the National Institute of Toxicology and Forensic Sciences (INTCF) from Madrid, aiming to provide proficiency tests for forensic DNA laboratories. Each annual exercise comprises a Basic (recently accredited under ISO/IEC 17043: 2010) and an Advanced Level, both including a kinship and a forensic module. Here, we show the results for both autosomal and sex-chromosomal STRs, and for mitochondrial DNA (mtDNA) in two samples included in the forensic modules, namely a mixture 2:1 (v/v) saliva/blood (M4) and a mixture 4:1 (v/v) saliva/semen (M8) out of the five items provided in the 2014 GHEP-ISFG IE. Discrepancies, other than typos or nomenclature errors (over the total allele calls), represented 6.5% (M4) and 4.7% (M8) for autosomal STRs, 15.4% (M4) and 7.8% (M8) for X-STRs, and 1.2% (M4) and 0.0% (M8) for Y-STRs. Drop-out and drop-in alleles were the main cause of errors, with laboratories using different criteria regarding inclusion of minor peaks and stutter bands. Commonly used commercial kits yielded different results for a micro-variant detected at locus D12S391. In addition, the analysis of electropherograms revealed that the proportions of the contributors detected in the mixtures varied among the participants. In regards to mtDNA analysis, besides important discrepancies in reporting heteroplasmies, there was no agreement for the results of sample M4. Thus, while some laboratories documented a single control region haplotype, a few reported unexpected profiles (suggesting contamination problems). For M8, most laboratories detected only the haplotype corresponding to the saliva. Although the GHEP-ISFG has already a large experience in IEs, the present multi-centric study revealed challenges that still exist related to DNA mixtures interpretation. Overall, the results emphasize the need for further research and training actions in order to improve the analysis of mixtures among the forensic practitioners.